Examining the feasibility, acceptability, validity and reliability of physical activity, sedentary behaviour and sleep measures in people with schizophrenia. (October 2021) - Berry, Alexandra; Drake, Richard J.; Butcher, Isabelle; Yung, Alison R.
Abstract: Background: Schizophrenia is associated with a more than doubled risk of death from cardiovascular disease (CVD). Risk factors for CVD include low levels of physical activity, sedentary behaviour and sleep problems. These risk factors are not systematically assessed by health services. Aims: Examine the feasibility, acceptability, validity and reliability of tools measuring physical activity, sedentary behaviour and sleep. Methods: Thirty participants with schizophrenia measured their physical activity, sedentary behaviour and sleep by wearing ActiGraph wGT3X-BT accelerometers on their wrist and waist, and recorded their sleep using the SleepBot smartphone app for 7 days. After 7 days they completed the 5-item Simple Physical Activity Questionnaire (SIMPAQ) to retrospectively measure their physical activity and sedentary behaviour over the study period. Concurrent SIMPAQ and SleepBot validity and inter-rater reliability were assessed against accelerometer-derived measures of physical activity, sedentary behaviour and sleep. A qualitative interview was conducted at the end of the study to assess acceptability. Results: The tools were feasible: 93% of participants provided valid wear-time accelerometry data and 83% provided SleepBot data. The SIMPAQ showed moderate concurrent validity but poor agreement for moderate-vigorous physical activity (MVPA) and moderate validity and agreement as a measure of sedentary behaviour. The SleepBot app showed poor concurrent validity and agreement for measures of sleep. The qualitative interviews demonstrated the tools were acceptable. Conclusion: Monitoring physical activity, sedentary behaviour and sleep by accelerometry, smartphone and questionnaire was feasible and acceptable to people with schizophrenia. The SIMPAQ could be a valid and appropriate tool for routine clinical use. Highlights: Low physical activity, sedentary behaviour and sleep problems are common in schizophrenia Measuring these lifestyle behaviours using accelerometry, a mobile phone app, and questionnaire is feasible and acceptable to people with schizophrenia The Simple Physical Activity Questionnaire (SIMPAQ) may provide a valid measure of moderate-vigorous physical activity and a valid and reliable measure of sedentary behaviour The SleepBot app did not demonstrate validity or agreement as a measure of sleep problems